Job Insecurity and Children's Emancipation - Sascha O. Becker; Samuel Bentolila; Ana Fernandes; Andrea Ichino (Center for Economic Studies and ifo Institute (CESifo), 2004)
The age at which children leave the parental home differs considerably across countries. We present a theoretical model predicting that higher job security of parents and lower job security of children may delay emancipation. We then provide aggregate evidence which supports this hypothesis for 12 European countries. We also give microeconometric evidence for Italy, the single country for which we have access to household-specific information on job security and coresidence. It is a very interesting case to study since, in the late 1990s, approximately 75 per cent of young Italians aged 18 to 35 were living at home and they had only a 4 per cent probability of emancipation in the subsequent 3 years. We show that this probability would have increased by 4 to 10 percentage points if their fathers had gone from having a fully secure job to becoming unemployed for sure.
Keywords: J10; J20; 330; emancipation; job security; option value